Global Trends and Future Outlooks in Centralized Exchange Research: A Comprehensive Bibliometric Review - Moch. Nuriko Firdaus; Ika Diyah Candra Arifah; Jorge Alberto Martinez Escandón (Journal of Digital Business and Innovation Management, 2026)
Centralized exchanges (CEX) serve as the most widely adopted cryptocurrency trading platforms in Indonesia. However, research on this topic rarely positions Indonesia as the object of study. Therefore, this study analyzes the development and challenges of CEX through a systematic review supported by bibliometric analysis in order to map future research topics relevant to Indonesia. The literature search was conducted using the Scopus database with the following keywords: ("cryptocurrency" OR "crypto" OR "digital asset" OR "cryptocurrencies") AND ("centralize" OR "centralized exchange" OR "centralized crypto asset exchanges" OR "CEX" OR "trading platform" OR "FTX"). The findings indicate that Indonesia presents contrasting outcomes between its global cryptocurrency adoption rate and the volume of research examining this topic within the country. Consequently, future research directions on this subject should prioritize cross-border collaborative efforts and expand the discourse of centralized exchanges (CEX) within the domains of infrastructure and technology, risk and security, market dynamics, and cryptocurrency trading regulations. Keywords: Centralized Exchange; Cryptocurrency; Bibliometric Analysis; Systematic Review